Application 0f Draft Tube in the Reduction of Backmixing Rate in Oscillatory Flow in a Baffled Column - Mohd Sobri Takriff; Zuhrina Masyitah (ASEAN Journal of Chemical Engineering, 2008)
Oscillatory flow in a baffled tube/column is an efficient way to enhance mixing in a straight smooth column. However, liquid oscillation moving back and forth across the baffle causes backmixing which is a disadvantage when plug flow is desired. This paper presents results from a study conducted to reduce the backmixing rate in oscillatory flow in a baffled column with the use of a draft tube. Results of this study showed that backmixing increases with oscillation velocity and decreases with liquid flow rate. The use of a draft tube reduces backmixing. The backmixing reduction is proportional to the ratio of L/Do However, the draft tube can not be extended too long because it disrupts the flow behavior in the column and creates dead zones near the baffle region. The draft tube length is maximized by extending it to both sides of the baffle, provided that the L/De on each side of the baffle is at 0.67 or less.